ESCOLAR DE 7 AÑOS CON FIEBRE Y HEPATOESPLENOMEGALIA, REPORTE DE CASO - Luna-Muñoz, Consuelo (2018)
Abstract Hemophagocytic lymphohistiocytosis (HLH), is rare, is caused by a dysfunction of cellular immunity by an alteration of NK cells (primary) or by an excessive proliferation of activated (secondary) macrophages. It is characterized by fever, hepatosplenomegaly, cytopenia, hemophagocytosis, hypertriglyceridemia and / or hypofibrinogenemia. In conclusion, in the presence of fever, hepatosplenomegaly and cytopenia, the diagnosis of hemophagocytic lymphohistiocytosis (HLH) should be considered. Key words: Fever; Hepatosplenomegaly; Cytopenia. (source: MeSH NLM) DOI: https://doi.org/10.25176/RFMH.v18.n1.1274